2012
DOI: 10.2147/ijn.s32154
|View full text |Cite
|
Sign up to set email alerts
|

In vivo tumor targeting and imaging with anti-vascular endothelial growth factor antibody-conjugated dextran-coated iron oxide nanoparticles

Abstract: Background Active targeting by specific antibodies combined with nanoparticles is a promising technology for cancer imaging and detection by magnetic resonance imaging (MRI). The aim of the present study is to investigate whether the systemic delivery of antivascular endothelial growth factor antibodies conjugating to the surface of functionalized supermagnetic iron oxide nanoparticles (anti-VEGF-NPs) led to target-specific accumulation in the tumor. Methods The VEGF ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Optimal MR imaging with SPIO particles depends on their magnetic properties, which, as studies have shown, depend on particle size and shape [181], [182]. SPIO particles functionalized with integrin targets [183] and VEGFR [184] have been used for molecular MR imaging of the tumor-associated endothelium. By further engineering of SPIO particles to form a chain, recent studies have shown targeting to tumor vascular integrins resulted in increased detection of breast tumor metastasis using MRI [85].…”
Section: Molecular Imaging Applicationsmentioning
confidence: 99%
“…Optimal MR imaging with SPIO particles depends on their magnetic properties, which, as studies have shown, depend on particle size and shape [181], [182]. SPIO particles functionalized with integrin targets [183] and VEGFR [184] have been used for molecular MR imaging of the tumor-associated endothelium. By further engineering of SPIO particles to form a chain, recent studies have shown targeting to tumor vascular integrins resulted in increased detection of breast tumor metastasis using MRI [85].…”
Section: Molecular Imaging Applicationsmentioning
confidence: 99%
“…(Table 1) Table 1. Gene therapy formulations with eluting drugs -Magneto-fluorescent silica nanoparticles (MFSN) [70] -Folic acid conjugated guar gum nanoparticles (MTXFA-GGNP) -Wheat germ agglutinin (WGA)-functionalised chitosan-Ca-alginate (CTS-Ca-ALG) microparticles (MPs) [71] -Anti-VEGF antibodyconjugated dextran-coated iron oxide nanoparticles (anti-EGF-NPs) [72] -HA modified mesoporous silica nanoparticles (HA-MSNs) [73] Discussion Current screening methodology is efficient, however; a novel approach regarding therapy is needed. Several efforts have been made towards identifying the genome of CRC cancer and therefore providing targeted therapy, mostly in the form of chemotherapy or inhibitors.…”
Section: Gene Therapymentioning
confidence: 99%
“…Active targeting resulted in higher accumulation in cancer cells with significantly improved contrast MR imaging [240]. Targeting ligands conjugated to MNP was exploited for theranostics purposes ranging from small molecule nutrient transporters such folate [241243] to macromolecules like Trastuzumab [244–246], single-chain anti-epidermal growth factor antibody [247], anti-epidermal growth factor receptor antibody [248], anti-vascular endothelial growth factor antibody (VEGF) [249, 250] and aptamers [251], [252]. A number of small molecular weight peptide have also been investigated including arginylglycylaspartic acid (RGD) [243, 253], bombesin [254, 255], and luteinizing hormone releasing hormone [256, 257]; highly cationic peptides like CPP [258], myristoylated poly-arginine peptide (MPAP) [259, 260] and HIV-TAT [261].…”
Section: Magnetic Nanoparticles (Mnp)mentioning
confidence: 99%